Writech: Enhancing Students’ Writing Skills Using the SAMR Model - Capangpangan, Bryan R. (Future Science / FSH-PH Publications, 2023)
Writing is one of the major competencies of 21st century skills that students need to develop. Accompanying the cultivation of this skill is the selection of timely methods involving the use of technology and educational platforms. In this study, the researcher undertook to realize the use of the SAMR model in enhancing the writing skills of the students of Meycauayan National High School – Senior High School. This study aims to assess the level of writing skills of students from the controlled and experimental groups. Using a quasi-experimental design, the study was conducted on 50 Grade 12 students from the ABM and HUMSS strands. In calculating the details, the researcher used a statistical method to obtain the weighted average mean and t-test measure to compare the results of the conducted preliminary and final tests, as well as the analysis of data in each category of writing. From the collected data, it was laid out in the study that after the intervention was carried out, the level of students' writing skills significantly increased. This study suggests the use of the SAMR model in developing the writing skills of students from different goals and strands of Senior High School. There were also some other problems related to other macro skills that need to be developed at the Filipino level and try to spread the use of technology and other educational platforms to bring out the best learning possibilities.